Effect of maternal nutrient intake during 31–37 weeks gestation on offspring body composition in Samoa. (16th November 2020) - Arslanian, Kendall J.; Fidow, Ulai T.; Atanoa, Theresa; Naseri, Take; Duckham, Rachel L.; McGarvey, Stephen T.; Choy, Courtney; Hawley, Nicola L.
Abstract: Background: Pregnancy dietary intake may be associated with newborn body composition, a predictor of future obesity. In Samoa, an energy-dense diet contributes to an alarming prevalence of adult obesity. Identifying associations between pregnancy nutrition and infant body composition in this setting may guide strategies to mitigate intergenerational transmission of obesity risk. Aim: To examine dietary macro- and micronutrient intake of Samoan women during the third trimester of pregnancy and associations with infant body composition. Subjects and methods: At 34–41 weeks of gestation, we measured dietary intake from the prior month using a Food Frequency Questionnaire (FFQ). Dual-energy X-ray absorptiometry (DXA) measured infant body composition at 1–14 days. We used multivariable linear regression models accounting for confounders to identify independent effects of nutrient intake on infant body composition. Results: After adjusting for maternal body mass index, age, gravidity, infant age, and sex, a respective 0.2 g increase and 0.2 g decrease in infant bone mass was associated with fibre and saturated fat intake. Increased protein intake was associated with 0.02 g decrease in bone mass. Conclusions: While maternal dietary intake was not associated with infant adiposity or lean mass, we observed an effect on bone mass whose role in regulating metabolic health is overlooked.